Evaluasi Rasionalitas Penggunaan Obat Antidiabetes pada Pasien Diabetes Melitus Tipe 2 dengan Komplikasi Hipertensi di Instalasi Rawat Inap Salah Satu Rumah Sakit Kota Cimahi: English - Linda Purnamawati Suherman; Diana Novalina; Pudjiastuti Kartidjo; Fauziah Nurul Afifah (Journal of Pharmaceutical and Sciences, 2026)
Type 2 diabetes mellitus (T2DM) with hypertension complications requires rational and standardized pharmacological management to prevent cardiovascular deterioration. This study aimed to evaluate the pattern and level of rationality of antidiabetic drug use in T2DM patients with hypertension complications in the inpatient ward of a hospital in Cimahi City for the period of January 2023 to December 2024. This study utilized a retrospective descriptive-analytical observational design involving 79 medical records that met the inclusion criteria. The assessment of rationality was measured using five parameters based on the Indonesian Ministry of Health guidelines: appropriate indication, drug selection, dosage, administration interval, and duration of therapy. The majority of patients were elderly females (62%). Prescribing patterns indicated that 50.6% of patients received a combination therapy of insulin and oral hypoglycemic drugs (OHDs), 31.7% received OHD monotherapy, and 12.6% received insulin monotherapy, with metformin and glimepiride being the most prescribed OHDs. The evaluation results of the rationality level reached 100% for the parameters of appropriate indication and duration of therapy, 96% for appropriate administration interval, 90% for appropriate dosage, and 70% for appropriate drug selection. The majority of inappropriateness stemmed from the selection of insulin regimens that had not been optimally individualized to the patients' clinical profiles. Overall, the antidiabetic management was classified as rational; however, a multidisciplinary approach and strong coordination between physicians and clinical pharmacists are crucial to optimize therapy individualization and adherence to standard guidelines.